What Will Be Best for Me? Big Decisions and the Problem of Inter‐World Comparisons. (24th August 2018) - Baumann, Peter
Abstract: Big decisions in a person's life often affect the preferences and standards of a good life which that person's future self will develop after implementing her decision. This paper argues that in such cases the person might lack any reasons to choose one way rather than the other. Neither preference‐based views nor happiness‐based views of justified choice offer sufficient help here. The available options are not comparable in the relevant sense and there is no rational choice to make. Thus, ironically, in many of a person's most important decisions the idea of that person's good seems to have no application.